KEBERPIHAKAN REPUBLIKA DAN MEDIA INDONESIA DALAM MEMBINGKAI KASUS PEMBAKARAN AL QUR'AN DALAM PEMBERITAANNYA - Handayani, Mediana (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2010)
This article is the result of research that raises issues of media bias inframing the case of burning the Quran in preaching. Media studied were newspaper Republika and Media Indonesia. This research will want to unload about how these two different views of the newspaper or the concept of peace, particularly regarding interreligious relations, raising events involving humiliation controversy over a particular religion. By basing the idea on the theory of Agenda Setting and using the analysis of Pan and Koiscki framing, it is known that in framing the plan of burning the Quran, both of Newspaper and Media Indonesia Republika, put forward the idea of ruling authority, in this case the politicians and the civil and religious leaders. This framing would not be discharged from investors and market taste factor.